2022
DOI: 10.1590/2526-8910.ctoao23023037
|View full text |Cite
|
Sign up to set email alerts
|

Substance use and meaning: transforming occupational participation and experience

Abstract: Introduction We draw on activity theory of concepts to examine ‘meaning of occupation’ and ‘substance use’ beyond preconceived notions of inherent positive or negative experiences. Objective To explore nuanced meanings of substance use and associated occupations. Method An online survey and semi-structured interviews were used to collect data from professionals about prevalence of substance use, substance effects, and personal experiences. In analyzing the interview data, we attended to substance use as a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…The 2017 Canadian Tobacco, Alcohol and Drugs Survey (CTADS) involved n = 16,349 telephone interviews conducted with residents aged 15 years and older ( Government of Canada, 2019a ). Our research about substance use among professionals has consistently found rates of past-year prevalence of substance use that well exceed what is reported in the CTADS study ( Kiepek, Ausman, et al, 2022 ; Kiepek et al, 2019 ). This may, in part, be accounted for by the anonymized nature of our online survey compared to phone interviews conducted by the federal government.…”
Section: Discussionmentioning
confidence: 41%
See 3 more Smart Citations
“…The 2017 Canadian Tobacco, Alcohol and Drugs Survey (CTADS) involved n = 16,349 telephone interviews conducted with residents aged 15 years and older ( Government of Canada, 2019a ). Our research about substance use among professionals has consistently found rates of past-year prevalence of substance use that well exceed what is reported in the CTADS study ( Kiepek, Ausman, et al, 2022 ; Kiepek et al, 2019 ). This may, in part, be accounted for by the anonymized nature of our online survey compared to phone interviews conducted by the federal government.…”
Section: Discussionmentioning
confidence: 41%
“…This, compounded by certain erroneous beliefs around substances, can be problematic. Reported separately, our study found that cocaine was used by 7% of Canadian professionals in the past-year and 19.8% ever ( Kiepek, Ausman, et al., 2022 ). Commonly reported effects included socializing enhanced, awake/alert, confidence, and energy increased, with no reports of work performance or missing work obligations.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Here, emphasis is placed on the aspects that compose a social perspective of drug use, going beyond understanding the specific effects of substances, and highlighting political and sociocultural contexts. The approach to drug use from a social point of view understands that there is not one substance or individual with similar elements, but rather different social and cultural contexts permeated by the use of different substances, and that without due attention to such differences, it is not possible to understand the theme in its entirety [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%